2015
DOI: 10.7763/ijcte.2015.v7.989
|View full text |Cite
|
Sign up to set email alerts
|

Application of Computed Tomography in Structure Analyses of Metal Matrix Syntactic Foams

Abstract: Abstract-In order to create 3D models used in finite element analysis, a reconstruction of the structure of metal foam composites reinforced with ceramic spherical shells is necessary. A new algorithm has been developed for reconstruction. The input of the algorithm consists of CT layer images which were created at the Szechenyi Istvan University, Györ, Hungary. The CT images were analyzed by the new algorithm. The algorithm seeks the contours of the spherical shells by gradually increasing the radii, also in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…The authors put ballast particles to a HDPE (water) tube (lined with single layer 1200 g/m 2 geotextile) with its original closing element and loaded by ZD-40 machine static to an ultimate loading value step by step. Before and after each loading stage, ballast samplewith all the particles in the tubeare scanned by a CT (computer tomography) equipment [7,10,11,25,26]. Because of loading a small aggregate, almost every particle's degradation is trackable.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The authors put ballast particles to a HDPE (water) tube (lined with single layer 1200 g/m 2 geotextile) with its original closing element and loaded by ZD-40 machine static to an ultimate loading value step by step. Before and after each loading stage, ballast samplewith all the particles in the tubeare scanned by a CT (computer tomography) equipment [7,10,11,25,26]. Because of loading a small aggregate, almost every particle's degradation is trackable.…”
Section: Purposementioning
confidence: 99%
“…Application of the CT (X-ray) equipment While there is a wide range of literature available for the 3-D image analysis, the authors found very little source related to testings of railway ballast and/or civil engineer granular materials with CT equipment. The CT (X-ray) equipment is available to the authors in the laboratory of Audi Hungaria Faculty of Automotive Engineering at Széchenyi István University, Győr (Hungary) [7,10,11,25,26].…”
Section: Individual Laboratory Testmentioning
confidence: 99%
“…Пено-металл обладает пористостью порядка 75-95 % [10], а его плотность в несколько раз ниже, чем у литого металла. По сути пенометалл -это одно-временно и новый вид конструкции, и новый вид спеченного материала [12].…”
Section: Introductionunclassified
“…Пенометалл обладает пористостью порядка 75-95 % [10], а его плотность в несколько раз ниже, чем у литого металла. По сути пенометалл -это одновременно и новый вид конструкции, и новый вид спеченного материала [12].…”
Section: Introductionunclassified